Role of weather on Alternaria Leaf Blight Disease and its effect on Yield and Yield Components of Mustard - Shrestha, Sundar K; Munk, Lisa; Mathur, Suresh B (Nepal Agriculture Research Journal, 2010)
Alternaria leaf blight disease caused by Alternaria brassicae in mustard (Brassica juncea (L) Czern and Coss) was studied in two crop seasons, 1992 and 1993 in Nepal at Nawalpur, Sarlahi (Tarai) and Khumaltar, Lalitpur (mid hill). At Nawalpur, epidemics of the disease was recorded for both seasons. Weather conditions like humidity, temperature and frequent rainfall played key role for the epidemics. In experimental fields, the disease appeared first in mid-December when the relative humidity was more than 80% with maximum temperature ranging between 18-25°C and minimum between 10-14°C. At Khumaltar, incidence of the disease was low in both seasons due to low average temperature from December to February. Among cultivars, Krishna and Pusabold were less susceptible than Varuna. Both mancozeb and iprodione had effectively reduced disease in the sprayed plots and increased seed yield by 48% and 130% respectively. The correlation between disease severity and yield, and yield components was negative and highly significant. Average yield loss was estimated to be in the range of 32 to 57%. Seed infection was also significantly higher in non sprayed treatment than sprayed one. The disease showed a negative effect on oil content causing losses on oil between 4.2 to 4.5%. Key words: Alternaria brassicae; epidemics; iprodione; mancozeb; mustard; oil content DOI: 10.3126/narj.v6i0.3366 Nepal Agriculture Research Journal Vol.6 2005 pp.62-72